Мінливість будови шлунка й кишечника у гібридів бантенга і бізона з домашньою коровою - Самчук, В.А.; Стекленьов, Є.П. (Фактори експериментальної еволюції організмів, 2014)
Aims. The aim of the investigation is to study the mutability and characteristics of structure and histostructure of stomach and bowel of the hybrids, obtained as a result of crossing bantengs and bisons with domestic cows. Methods. Stomachs and bowels of bantengs, bisons, and domestic cows of Red Steppe Breed, Grey Ukrainian Breed and their hybrids, which are kept in Askania-Nova in conditions of half-loose housing, were used in the investigation. According to the absolute data of stomach, bowel and their segments’ weight, the indices of relative organ formation were defined. For histological investigation the samples of stomach, large and small bowel segments were fixed in formalin, embedded in celloidin, stained by hematoxylin and eosin. Nonparametric techniques were used for making statistic analysis. Results. Stomach and bowels of hybrids of wild bantengs, bisons, and domestic cows had significant mutability in weight, both in absolute and relative measures. The correlation of the segments of stomach, large and small bowel, intestinal lining and layers of intestinal wall had definite difference in animals’ ontogenesis and in dependence on the types of crossing. Conclusions. Mulability of the organs of digestive system in hybrid animals contributes to succeeding in adaptation of digestion to heterogeneous feeding–stuffs, and in adapting to seasonal changes or new habitat.